Children and adolescents' attitudes towards sugar reduction in dairy products. (April 2017) - Yoo, Hye-Jong; Machín, Leandro; Arrúa, Alejandra; Antúnez, Lucía; Vidal, Leticia; Giménez, Ana; Curutchet, María Rosa; Ares, Gastón
Abstract: The development of strategies to reduce sugar intake of children and adolescents has been deemed necessary to cope with the global obesity epidemic. In this context, the aims of the present work were to study attitudes towards sugar reduction in three dairy products of children and adolescents of two income levels and to assess if these attitudes were modulated by the inclusion of the traffic light system on labels. A total of 646 children and adolescents from three primary/secondary schools in Montevideo (Uruguay) participated in the study. A total of twelve labels were designed following a full factorial design with three variables: dairy product (3 levels: yogurt, chocolate-flavoured milk and vanilla milk dessert), sugar reduction claim (2 levels: absent and present "20% less sugar") and traffic light system (2 levels: absent and present). Children had to evaluate their expected liking of the labels and to answer a check-all-that-apply question composed of terms related to tastiness, healthfulness and fun. Sugar claim significantly increased children and adolescents' expected liking scores ( p  = 0.01), suggesting they had a positive attitude towards sugar reduction in the evaluated dairy products. However, the influence of sugar reduction claim on hedonic expectations and healthfulness perception was modulated by the inclusion of the traffic-light system on labels ( p  = 0.01). This front-of-pack nutrition labelling scheme increased their unhealthfulness perception of products with high sugar content and could potentially discourage their consumption. Age and income modulated the influence of these strategies on hedonic and healthfulness perception ( p  < 0.05). Highlights: Children and adolescents' perception of sugar reduced dairy products was assessed. 646 children and adolescents completed a rating-based conjoint task with labels. Children and adolescents had a positive attitude towards sugar reduction. The traffic-light system decreased healthfulness perception of high-sugar products. Age and income modulated the influence of sugar reduction and nutrition information.